Akupresur Dapat Mengurangi Mual dan Muntah pada Pasien Kanker Payudara: Tinjauan Literatur Sistematis - Mula Tarigan; Nafi Yannis; Cahaya Gultom (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2024)
Nausea and vomiting is a complaint that often occurs in cancer patients undergoing chemotherapy. Even though he had received antiemetic therapy before giving chemotherapy, this complaint still appeared and even dominated the other complaints. So complementary therapies are needed to accompany the medical therapy provided to achieve holistic care in patient care. One complementary therapy that is very effective in reducing nausea and vomiting is acupressure. This study aims to conclude the importance of acupressure intervention in reducing complaints of nausea and vomiting in breast cancer patients. Searching for articles in this systematic literature review used the PRISMA method, which focuses on acupressure interventions in reducing nausea and vomiting. The search strategy used Boolean Search with keywords acupressure AND breast cancer OR breast cancer AND nausea and vomiting. The author selected the articles collected according to the determination of keywords in the inclusion and exclusion criteria. Six databases were searched from Proquest, ScienceDirect, CINAHL, Pubmed, Google Scholar, and SpringerLink sites from 2019-2023, and all articles were evaluated according to relevance and research quality. 15 articles have been analyzed according to characteristics, interventions, nausea and vomiting instruments used, and research objectives from 7 articles of international and 8 national reputations. This systematic literature review study significantly resulted in the conclusion that complementary acupressure therapy can reduce complaints of nausea and vomiting in breast cancer patients. Acupressure intervention can be used as evidence-based practice in improving holistic patient care